Safety of teriflunomide in Chinese adult patients with relapsing multiple sclerosis: A phase IV, 24-week multicenter study - Quan Chao; Zhou Hongyu; Yang Huan; Jiao Zheng; Zhang Meini; Zhang Baorong; Tan Guojun; Bu Bitao; Jin Tao; Li Chunyang; Xue Qun; Dong Huiqing; et al. (中华医学杂志英文版, 2025)
Background::Disease-modifying therapies have been approved for the treatment of relapsing multiple sclerosis (RMS). The present study aims to examine the safety of teriflunomide in Chinese patients with RMS.Methods::This non-randomized, multi-center, 24-week, prospective study enrolled RMS patients with variant (c.421C>A) or wild type ABCG2 who received once-daily oral teriflunomide 14 mg. The primary endpoint was the relationship between ABCG2 polymorphisms and teriflunomide exposure over 24 weeks. Safety was assessed over the 24-week treatment with teriflunomide. Results::Eighty-two patients were assigned to variant ( n = 42) and wild type groups ( n = 40), respectively. Geometric mean and geometric standard deviation (SD) of pre-dose concentration (variant, 54.9 [38.0] μg/mL; wild type, 49.1 [32.0] μg/mL) and area under plasma concentration-time curve over a dosing interval (AUC tau) (variant, 1731.3 [769.0] μg·h/mL; wild type, 1564.5 [1053.0] μg·h/mL) values at steady state were approximately similar betw